Low-temperature crosslinking process of crosslinked polyethylene insulating material

By modifying the base resin composition and the synergistic crosslinking system, combined with segmented microwave pretreatment and nitrogen replacement, the problems of low-temperature crosslinking efficiency and poor uniformity were solved, achieving efficient preparation of medium and high voltage cables and improving the overall performance and production efficiency of insulation materials.

CN121293619APending Publication Date: 2026-01-09JIANGSU HUACHUANG CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511747760.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing low-temperature crosslinking processes suffer from low crosslinking efficiency, poor crosslinking uniformity, and limited applicability, making it difficult to meet the high-end application requirements of medium and high voltage cables.

Method used

A modified base resin composition and a synergistic crosslinking system are used, including metallocene linear low-density polyethylene, branching-controlled high-density polyethylene, functionalized grafted polyolefin elastomer and surface-modified nano silica, combined with a composite antioxidant system, multi-component composite peroxide initiator and silane crosslinking agent, and through segmented microwave pretreatment and sealed nitrogen replacement, temperature, humidity and pressure are precisely controlled to achieve low-temperature uniform crosslinking.

Benefits of technology

It achieves efficient and uniform low-temperature crosslinking, improving electrical insulation performance, mechanical strength and environmental stability. It is suitable for the efficient preparation of thick-walled and thin-walled insulation materials, reducing production costs and energy consumption, and is adapted to large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293619A_ABST
    Figure CN121293619A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature crosslinking process of a crosslinked polyethylene insulating material, and relates to the technical field of cable insulating material preparation. The process comprises the following steps: preparing a crosslinking premix containing a modified basic resin composition and a synergistic crosslinking system, carrying out melt blending and molding to obtain an insulating base material, optimizing the reaction activity of the base material through sectional microwave pretreatment, and carrying out low-temperature crosslinking reaction in a sealed environment through nitrogen replacement and in a saturated nitrogen atmosphere to obtain the high-temperature-resistant insulating material. And finally, carrying out gradient humidifying and cooling treatment to obtain the product. According to the process, the problems of low crosslinking degree, poor uniformity and the like of the existing process are solved through combination of resin modification, collaborative crosslinking system construction, sectional pretreatment and crosslinking environment regulation and control, and the process is suitable for efficient preparation of the high-voltage cable insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable insulation material preparation technology, specifically relating to a low-temperature crosslinking process for crosslinked polyethylene insulation material. Background Technology

[0002] Cross-linked polyethylene (XLPE) is the mainstream material in the cable insulation field. Low-temperature cross-linking technology, due to its advantages such as low energy consumption and mild equipment requirements, has become a key development direction in the industry. Currently, low-temperature cross-linking technologies mainly include silane cross-linking, irradiation cross-linking, and ultraviolet (UV) cross-linking. Among these, silane cross-linking is the most widely used. However, traditional silane cross-linking processes rely on long-term water treatment, resulting in low cross-linking efficiency and uneven cross-linking within the substrate, affecting the electrical performance stability of the insulation material. While irradiation and UV cross-linking do not require a water environment, their limitations in cross-linking depth make them unsuitable for preparing thick-walled insulation substrates, and their high equipment investment costs restrict their large-scale application in medium and high voltage cables.

[0003] The core problems of existing low-temperature crosslinking processes focus on three aspects: resin system compatibility, crosslinking system activity, and process synergy. The base resin often uses a single system of ordinary polyethylene or a simple blend, resulting in insufficient reactivity with the crosslinking agent. This needs to be compensated for by increasing the temperature or extending the time, thus limiting production efficiency. The crosslinking system often relies on a single type of crosslinking agent and catalyst, lacking a synergistic mechanism, which easily leads to localized over- or under-crosslinking. Furthermore, the generation of byproducts may affect the long-term insulation performance of the material. In addition, the lack of effective coordination between process steps, the simplistic pretreatment methods, and the imprecise control of temperature, humidity, and gas atmosphere in the crosslinking reaction environment further exacerbate the problem of poor crosslinking uniformity.

[0004] With the increasing voltage and efficiency of power transmission, higher demands are being placed on the comprehensive performance of cross-linked polyethylene insulation materials. These materials require not only excellent electrical insulation properties but also good mechanical strength and environmental stability. Existing low-temperature cross-linking processes struggle to balance cross-linking efficiency, product quality, and production costs, failing to meet the needs of high-end applications such as medium- and high-voltage cables. Therefore, developing a technical solution that achieves efficient and uniform low-temperature cross-linking through resin modification, synergistic cross-linking system construction, and process optimization has become a pressing technical challenge in the field of cable insulation materials. Summary of the Invention

[0005] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a low-temperature crosslinking process for crosslinked polyethylene insulation materials, which solves the problems of low low-temperature crosslinking efficiency, poor crosslinking uniformity, and limited applicability in the prior art.

[0006] To address the above problems, the present invention provides the following technical solution: A low-temperature crosslinking process for crosslinked polyethylene insulation material includes the following steps: S1. Prepare a modified base resin composition, wherein, by weight, the modified base resin composition comprises 55-70 parts of metallocene linear low-density polyethylene, 8-12 parts of high-density polyethylene with a branching degree of 0.8-1.2, 12-22 parts of ethylene-octene copolymer grafted with maleic anhydride, 2-4 parts of nano-silica with surface grafted with methacryloyloxypropyltrimethoxysilane, and 0.5-1.0 parts of a composite antioxidant system. Add each component to a high-speed mixer and mix for 20-30 minutes at a speed of 1000-1400 r / min and a temperature of 85-100℃ to obtain a homogeneous mixture. S2. The mixture obtained in step S1 is added to a twin-screw extruder for melt blending. The barrel temperature of the twin-screw extruder is set sequentially from the feed end to the die head as 135℃, 145℃, 155℃, 165℃, and 170℃. The screw speed is 350r / min to 500r / min, and the die head pressure is controlled at 20MPa to 30MPa. After extrusion, the mixture is cooled in a cooling water tank with a water temperature of 25℃ to 35℃, and then pelletized by a pelletizer to obtain modified base resin particles. S3. Prepare a synergistic crosslinking system, wherein, by mass, the synergistic crosslinking system comprises 3-5 parts of vinyltriisopropoxysilane, 0.2-0.4 parts of a composite peroxide initiator, 0.1-0.2 parts of isopropyltris(dioctylpyrophosphate)titanate, 1.5-2.5 parts of pentaerythritol tetraacrylate, and 0.3-0.6 parts of N-phenylmaleimide. Mix the components at 25℃-30℃ for 8-15 minutes at a stirring rate of 300-400 r / min to obtain a uniform synergistic crosslinking agent. S4. Add the modified base resin particles obtained in step S2 and the synergistic crosslinking agent obtained in step S3 to a pressure mixer at a mass ratio of 100:6~100:9. Mix for 10min~15min at a temperature of 115℃~130℃, a speed of 70r / min~100r / min, and a pressure of 0.4MPa~0.8MPa. During the mixing process, nitrogen purging is performed every 3min for 30s each time to obtain the crosslinked premix. S5. The crosslinked premix obtained in step S4 is added to a single-screw extruder. The extruder barrel temperature is set sequentially from the feed end to the die head to 125℃, 135℃, 145℃, and 155℃. The screw speed is 180r / min to 280r / min, and the die head temperature is 150℃ to 165℃. The material is formed through an extrusion die with a die head pressure of 18MPa to 28MPa and an extrusion speed of 12m / min to 25m / min to obtain an insulating substrate. S6. Perform segmented microwave pretreatment on the insulating substrate obtained in step S5. The first segment uses a microwave frequency of 2450MHz, a power of 350W~450W, a processing time of 2min~4min, and maintains the substrate temperature at 65℃~70℃. The second segment uses a microwave frequency of 915MHz, a power of 400W~550W, a processing time of 3min~5min, and maintains the substrate temperature at 70℃~78℃. S7. Place the pretreated insulating substrate in a sealed crosslinking reaction chamber. First, purge the air in the chamber with nitrogen gas of 99.99% purity three times, with each purging time being 15 minutes. After the purging is completed, purge the chamber with saturated nitrogen gas of 88%~96% humidity. Control the reaction temperature at 78℃~88℃ and the pressure inside the chamber at 0.15MPa~0.3MPa. Maintain these conditions for the crosslinking reaction for 5h~9h. S8. After the crosslinking reaction is completed, keep nitrogen gas flowing through the chamber and reduce the humidity in the reaction chamber to 45%~55% at a rate of 5% per hour. At the same time, reduce the temperature to 30℃~35℃ at a rate of 3℃ / min~6℃ / min and keep it at that temperature for 40min~70min. Then stop the nitrogen flow and allow it to cool naturally to room temperature to obtain crosslinked polyethylene insulation material.

[0007] Furthermore, the composite antioxidant system in step S1 is composed of a hindered thiophenolic antioxidant, a phosphite antioxidant, and a hindered amine light stabilizer in a mass ratio of 3:2:1. Here, the hindered thiophenolic antioxidant captures free radicals generated during processing, the phosphite antioxidant decomposes hydrogen peroxide, and the hindered amine light stabilizer inhibits degradation caused by photoaging. The combination of these three components prevents oxidative degradation of the resin during high-temperature melting, low-temperature crosslinking, and subsequent use, ensuring the long-term stability of the material.

[0008] Furthermore, in step S1, the surface-grafted methacryloyloxypropyltrimethoxysilane nano-silica has a grafting rate of 8%~12% and a particle size of 30nm~60nm. The grafting rate and particle size range are clearly defined here. The grafting rate ensures the compatibility of the nano-silica with the resin matrix, avoiding agglomeration that leads to stress concentration. The particle size selection allows the nanoparticles to be uniformly dispersed in the matrix, forming stable physical cross-linking points, while simultaneously improving the material's breakdown strength and mechanical strength, enhancing its insulation performance and structural stability.

[0009] Furthermore, in step S1, the grafting rate of the ethylene-octene copolymer grafted with maleic anhydride is 1.5%~2.5%, and the melt flow rate is 1.2g / 10min~2.0g / 10min. The selection of this grafting rate and melt flow rate ensures compatibility with the polyethylene matrix, promotes interactions between molecular chains, optimizes the processing fluidity of the resin system, results in more uniform melt blending, and improves the material's resistance to environmental stress cracking, preventing cracks from forming in the insulating material during long-term use due to stress.

[0010] Furthermore, in step S2, the twin-screw extruder has an aspect ratio of 40:1 and a screw compression ratio of 3.5:1. These aspect ratio and screw compression ratio settings ensure that the mixture is fully melted, sheared, and dispersed within the barrel, extending the material residence time and resulting in more uniform mixing of the components. This avoids excessively high or low concentrations of certain components in certain areas, laying the foundation for the uniformity of the subsequent crosslinking reaction and improving the molding quality of the resin particles.

[0011] Further, in step S3, the composite peroxide initiator is composed of di-tert-butyl peroxide, 1,3-di-tert-butylperoxyisopropylbenzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane in a mass ratio of 2:1:1. Here, the three peroxides are compounded in a specific ratio, utilizing the differences in decomposition temperature and rate of different peroxides to form a continuous free radical release curve. This continuously provides active free radicals within the low-temperature crosslinking range, avoiding excessively fast or slow crosslinking rates caused by a single initiator, ensuring a stable crosslinking reaction, and improving crosslinking uniformity and degree of crosslinking.

[0012] Furthermore, in step S4, the nitrogen purging pressure of the internal mixer is 0.6 MPa to 0.9 MPa. This purging pressure can effectively remove volatile byproducts and air generated during the internal mixing process, avoiding residual air from affecting the crosslinking reaction activity. At the same time, it prevents byproducts from accumulating in the material and causing a decrease in insulation performance, thus ensuring the purity and reactivity of the crosslinked premix.

[0013] Furthermore, in step S5, the die expansion ratio of the extrusion die is 1.8:1 to 2.2:1, and the die temperature is maintained at 155℃ to 160℃. This control of the die expansion ratio and die temperature ensures dimensional stability of the insulating substrate during extrusion molding, avoids uneven substrate thickness due to improper expansion ratio, and maintains a smooth substrate surface and dense internal structure, reducing molding defects and improving the mechanical and insulating properties of the substrate.

[0014] Furthermore, in step S7, the rate at which saturated nitrogen is introduced is 0.8 m³ / s. 3 / h~1.8m 3 / h. A reasonable inlet rate here ensures a stable humidity and pressure environment within the reaction chamber, providing a sufficient reaction atmosphere for the crosslinking reaction. It also allows for the timely removal of trace byproducts generated during the reaction, preventing their accumulation from affecting the crosslinking effect. Simultaneously, it ensures a consistent reaction environment across all parts of the substrate, improving crosslinking uniformity.

[0015] Furthermore, in step S7, during the crosslinking reaction, the temperature and humidity are calibrated every 45 minutes using an online monitoring system. The temperature deviation is controlled within ±0.8℃, and the humidity deviation is controlled within ±2%. This periodic calibration of temperature and humidity and control of deviation ranges ensures that the crosslinking reaction always proceeds under optimal conditions, avoiding localized insufficient or excessive crosslinking due to fluctuations in environmental parameters. This guarantees consistent crosslinking quality across all products and improves the stability and reliability of mass production.

[0016] The present invention discloses a low-temperature crosslinking process for crosslinked polyethylene insulation materials. This invention constructs an adaptive system of modified base resin composition and synergistic crosslinking system. A specific ratio of metallocene linear low-density polyethylene, branched high-density polyethylene, functionalized grafted polyolefin elastomer, and surface-modified nanofiller are used as the resin matrix. A composite antioxidant system is used to ensure processing and use stability. At the same time, a multi-component composite peroxide initiator, silane crosslinking agent, multifunctional crosslinking aid, and high-efficiency catalyst are used to form a synergistic crosslinking system. The substrate reaction activity is optimized by segmented microwave pretreatment. Low-temperature uniform crosslinking is achieved by nitrogen replacement in a sealed environment and a saturated nitrogen atmosphere with precise control of temperature, humidity, and pressure. Gradient humidity and cooling treatment is then used to reduce internal stress, ultimately achieving a synergistic improvement in crosslinking degree, mechanical strength, and environmental stability.

[0017] Compared with the prior art, the advantages of the present invention are as follows: (1) This invention utilizes the synergistic effect of composite peroxide initiator, silane crosslinking agent, and multifunctional crosslinking aid, combined with segmented microwave pretreatment to optimize the substrate reactivity, thereby significantly shortening the low-temperature crosslinking reaction cycle and avoiding performance loss caused by high-temperature processing, thus balancing production efficiency and process gentleness. (2) This invention relies on the compatibility optimization of each component in the modified base resin composition and the uniform dispersion of nanofillers. Combined with the crosslinking atmosphere of nitrogen replacement, precise temperature, humidity and pressure control in a sealed environment, it effectively avoids local insufficient or excessive crosslinking and ensures the consistency of the crosslinking network inside the material. (3) The introduction of functionalized grafted polyolefin elastomer and surface modified nanofiller in this invention, combined with the protective effect of composite antioxidant system, enables the product to have excellent electrical insulation performance, mechanical strength and environmental stress cracking resistance, and meet the stringent requirements of medium and high voltage cables. (4) The twin-screw extruder parameters of the present invention are optimized to achieve full melting and dispersion of materials, nitrogen purging during the mixing process reduces the accumulation of by-products, and gradient humidity conditioning and cooling treatment reduces internal stress, which greatly reduces the risk of material degradation during processing and long-term service and extends service life. (5) This invention breaks through the limitations of traditional low-temperature crosslinking process on the thickness of insulating substrate, and achieves efficient preparation of thick-walled and thin-walled insulating materials through process synergistic innovation. At the same time, it does not require special high-end equipment, adapts to the needs of large-scale production, and lowers the application threshold. (6) The low-temperature crosslinking process of the present invention reduces energy consumption, nitrogen atmosphere and gradient treatment reduce pollutant emissions, and the composite system optimization reduces the amount of additives used. While improving product performance, it also reduces production costs, achieving a balance between technical economy and environmental friendliness. Attached Figure Description

[0018] Figure 1 This is a flowchart of a low-temperature crosslinking process for a crosslinked polyethylene insulation material according to the present invention. Detailed Implementation

[0019] To facilitate understanding of the present invention, the invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0020] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0021] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0022] Example 1 refer to Figure 1 A low-temperature crosslinking process for the crosslinked polyethylene insulation material of the present invention includes the following steps. S1. Prepare a modified base resin composition. By mass, the modified base resin composition comprises 68.3 parts of metallocene linear low-density polyethylene, 10 parts of high-density polyethylene with a branching degree of 1.0, 18 parts of ethylene-octene copolymer grafted with maleic anhydride, 3 parts of nano-silica with surface grafted with methacryloyloxypropyltrimethoxysilane, and 0.7 parts of a composite antioxidant system. The composite antioxidant system is composed of thiohedral hindered phenolic antioxidant, phosphite antioxidant, and hindered amine light stabilizer in a mass ratio of 3:2:1. The surface grafting rate of nano-silica with surface grafted with methacryloyloxypropyltrimethoxysilane is 10%, and the particle size is 45 nm. The grafting rate of ethylene-octene copolymer grafted with maleic anhydride is 2.0%, and the melt flow rate is 1.6 g / 10 min. Add each component to a high-speed mixer and mix for 25 min at a speed of 1200 r / min and a temperature of 92 °C to obtain a homogeneous mixture. S2. The mixture obtained in step S1 is added to a twin-screw extruder for melt blending. The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw compression ratio is 3.5:1, the barrel temperature is set sequentially from the feed end to the die head at 135℃, 145℃, 155℃, 165℃, and 170℃, the screw speed is 420 r / min, and the die head pressure is controlled at 25 MPa. After extrusion, the mixture is cooled in a cooling water tank at 30℃ and then pelletized by a pelletizer to obtain modified base resin granules. S3. Prepare a synergistic crosslinking system. By mass, the synergistic crosslinking system comprises 4 parts vinyltriisopropoxysilane, 0.3 parts composite peroxide initiator, 0.15 parts isopropyltris(dioctylpyrophosphonooxy)titanate, 2 parts pentaerythritol tetraacrylate, and 0.45 parts N-phenylmaleimide. The composite peroxide initiator is composed of di-tert-butyl peroxide, 1,3-di-tert-butylperoxyisopropylbenzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane in a mass ratio of 2:1:1. The components are stirred and mixed at 28°C for 12 min at a stirring rate of 350 r / min to obtain a uniform synergistic crosslinking agent. S4. Add the modified base resin particles obtained in step S2 and the synergistic crosslinking agent obtained in step S3 to a pressure mixer at a mass ratio of 100:7.5. Mix for 13 minutes at a temperature of 122℃, a speed of 85 r / min, and a pressure of 0.6 MPa. Nitrogen purging is performed every 3 minutes during the mixing process, with each purging time being 30 seconds and a nitrogen purging pressure of 0.75 MPa, to obtain the crosslinked premix. S5. The cross-linked premix obtained in step S4 is added to a single-screw extruder. The extruder barrel temperature is set sequentially from the feed end to the die head to 125℃, 135℃, 145℃, and 155℃. The screw speed is 230 r / min, the die head temperature is 158℃, and the material is formed through an extrusion die with a die head pressure of 23 MPa. The die opening ratio of the extrusion die is 2.0:1, the die temperature is maintained at 158℃, and the extrusion speed is 18 m / min to obtain an insulating substrate. S6. Perform segmented microwave pretreatment on the insulating substrate obtained in step S5. The first segment uses a microwave frequency of 2450MHz, a power of 400W, and a processing time of 3min, while maintaining the substrate temperature at 68℃. The second segment uses a microwave frequency of 915MHz, a power of 480W, and a processing time of 4min, while maintaining the substrate temperature at 74℃. S7. Place the pretreated insulating substrate in a sealed cross-linking reaction chamber. First, purge the air in the chamber three times with 99.99% pure nitrogen gas, each purge lasting 15 minutes. After the purge is complete, purge the reaction chamber with 92% humidity saturated nitrogen gas at a purge rate of 1.3 m / s. 3 / h, control the reaction temperature at 83℃ and the pressure inside the chamber at 0.22MPa, maintain these conditions for 7h of crosslinking reaction, and calibrate the temperature and humidity through the online monitoring system every 45min during the crosslinking reaction, with the temperature deviation controlled within ±0.8℃ and the humidity deviation controlled within ±2%. S8. After the crosslinking reaction is completed, keep nitrogen gas flowing in and reduce the humidity in the reaction chamber to 50% at a rate of 5% per hour, while reducing the temperature to 32℃ at a rate of 4.5℃ / min. Keep the temperature for 55 minutes, then stop the nitrogen flow and allow it to cool naturally to room temperature to obtain crosslinked polyethylene insulation material.

[0023] Example 2 The difference between this embodiment and Embodiment 1 is that the modified base resin composition in step S1 is adjusted to consist of 64.7 parts of metallocene linear low-density polyethylene, 11 parts of high-density polyethylene with a branching degree of 0.9, 20 parts of ethylene-octene copolymer grafted with maleic anhydride, 3.5 parts of nano-silica with surface grafted with methacryloyloxypropyltrimethoxysilane, and 0.8 parts of composite antioxidant system; the parameters and technical features of the remaining steps are the same as those in Embodiment 1.

[0024] Example 3 The difference between this embodiment and Embodiment 1 is that the segmented microwave pretreatment parameters in step S6 are adjusted as follows: the first segment has a microwave power of 400W and a processing time of 3 minutes, maintaining a substrate temperature of 67°C; the second segment has a microwave power of 500W and a processing time of 4 minutes, maintaining a substrate temperature of 75°C. In step S7, the crosslinking reaction temperature is adjusted to 83°C, the reaction time to 7 hours, and the saturated nitrogen gas introduction rate to be 1.5 m / s². 3 / h, the pressure inside the chamber is controlled at 0.25MPa, and the online monitoring calibration frequency and deviation control during the crosslinking reaction are consistent with those in Example 1; the parameters and technical features of the remaining steps are the same as those in Example 1.

[0025] Comparative Example 1 The difference between this comparative example and Example 1 is that the N-phenylmaleimide component is removed from the synergistic crosslinking system prepared in step S3, and the composite peroxide initiator is replaced with a single di-tert-butyl peroxide, with the amount still being 0.3 parts; the types, amounts, and mixing conditions of other components in the synergistic crosslinking system are the same as in Example 1, and the technical features and parameters of the remaining steps are the same as in Example 1.

[0026] Comparative Example 2 The difference between this comparative example and Example 1 is that the segmented microwave pretreatment process in step S6 is omitted, and the insulating substrate obtained in step S5 is directly transferred to the sealed crosslinking reaction chamber in step S7 for crosslinking reaction; the crosslinking reaction conditions in step S7 and the technical features and parameters of subsequent steps are the same as in Example 1.

[0027] Comparative Example 3 The difference between this comparative example and Example 1 is that the modified base resin composition in step S1 is replaced with 70 parts of ordinary linear low-density polyethylene, 15 parts of high-density polyethylene, and 15 parts of ungrafted ethylene-octene copolymer, and the nano-silica and composite antioxidant system are omitted; the speed, temperature and mixing time of the high-speed mixer during the mixing process are still the same as in Example 1, and the technical features and parameters of the remaining steps are the same as in Example 1.

[0028] Comparative Example 4 The difference between this comparative example and Example 1 is that the nitrogen replacement operation is omitted in step S7, the pressure inside the reaction chamber is not controlled, and the crosslinking reaction is carried out in a conventional open water environment. The water environment temperature is consistent with the crosslinking reaction temperature of Example 1. The amount of isopropyltris(dioctylpyrophosphoryloxy)titanate in the synergistic crosslinking system remains unchanged, and the technical features and parameters of the remaining steps are the same as those of Example 1.

[0029] The insulating materials in Examples 1-3 and Comparative Examples 1-4 were tested using the following methods: 1. Degree of cross-linking: Soxhlet extraction was used with xylene as solvent to extract the uncross-linked soluble fraction, and the degree of cross-linking was calculated by mass loss. 2. Tensile strength and elongation at break: According to GB / T1040.3-2006, the test was conducted using a universal testing machine at a tensile rate of 50 mm / min. 3. Heat distortion temperature: According to GB / T1633-2000, the temperature at which the deformation of the sample reaches 0.32 mm is determined under a load of 0.45 MPa and a heating rate of 120℃ / h. 4. Dielectric strength: Referring to GB / T1408.1-2016, the electric field strength at the breakdown point of the sample was determined by the oil immersion method at a voltage increase rate of 2kV / s. 5. Low-temperature impact strength: According to GB / T1843-2008, the impact absorption energy of an unnotched specimen is determined using a simply supported beam impact testing machine at -40℃ and converted into impact strength. 6. Thermal aging tensile retention rate: The sample was placed in a thermal aging chamber at 135℃ for 168h, and the tensile strength before and after aging was tested according to GB / T1040.3-2006, and the retention rate was calculated. 7. Volume resistivity: Refer to GB / T1410-2006, use a high-resistivity meter, and measure with a DC voltage of 500V at 23℃ and 50% relative humidity.

[0030] Table 1: Experimental Results of Examples 1-3 and Comparative Examples 1-4

[0031] In summary, referring to Table 1, the key performance indicators of the embodiments, such as crosslinking degree, tensile strength, and dielectric strength, are significantly better than those of the comparative examples, fully demonstrating the performance improvement brought about by the present invention through process innovations such as modified base resin composition, synergistic crosslinking system, and segmented microwave pretreatment.

[0032] Comparative Example 1, lacking N-phenylmaleimide and using a single peroxide initiator, resulted in insufficient synergistic effect of the crosslinking system, discontinuous free radical release, and low crosslinking degree, thus affecting various mechanical and electrical properties. Comparative Example 2, by omitting segmented microwave pretreatment, failed to optimize the substrate reactivity, reduced the uniformity of the crosslinking reaction, and limited performance. Comparative Example 3, using unmodified resin and lacking nano-silica and a composite antioxidant system, suffered from insufficient resin compatibility and structural stability, incomplete crosslinking network construction, and poor overall performance. Comparative Example 4, by not performing nitrogen replacement and using an open water environment for crosslinking, had inaccurate control of temperature, humidity, and pressure in the reaction environment, easily leading to the accumulation of byproducts, resulting in unsatisfactory crosslinking efficiency and performance.

[0033] Example 1 achieves uniform construction of crosslinked network and balanced performance improvement by optimizing the ratio of modified base resin, synergistic crosslinking system components and various process parameters.

[0034] Example 2: The ratio of the modified base resin composition was adjusted to optimize the elongation at break and low-temperature impact strength while ensuring crosslinking efficiency.

[0035] Example 3 optimized the segmented microwave pretreatment and crosslinking reaction parameters, further improving the degree of crosslinking, tensile strength and dielectric strength.

Claims

1. A low temperature crosslinking process for crosslinking polyethylene insulation material, characterized in that: Comprising the following steps, S1. Preparing a modified base resin composition, the modified base resin composition comprising, by mass parts, metallocene linear low density polyethylene 55-70 parts, high density polyethylene with a branching degree of 0.8-1.2 8-12 parts, ethylene-octene copolymer grafted maleic anhydride 12-22 parts, nano-silica surface grafted methacryloyloxypropyl trimethoxysilane 2-4 parts, a composite antioxidant system 0.5-1.0 parts, each component is added to a high-speed mixer and mixed at a speed of 1000 r / min-1400 r / min and a temperature of 85℃-100℃ for 20 min-30 min to obtain a uniform mixture; S2. The mixture obtained in step S1 is added to a twin-screw extruder for melt blending, the barrel temperature of the twin-screw extruder is set to 135℃, 145℃, 155℃, 165℃, 170℃ from the feeding end to the head direction, the screw speed is 350 r / min-500 r / min, the head pressure is controlled to be 20 MPa-30 MPa, after extrusion, the material is cooled in a cooling water tank with water temperature of 25℃-35℃, then granulated by a granulator to obtain modified base resin particles; S3. Preparing a synergistic crosslinking system, the synergistic crosslinking system comprising, by mass parts, vinyl triisopropoxy silane 3-5 parts, composite peroxide initiator 0.2-0.4 parts, isopropyl tri(dioctyl pyrophosphoryloxy) titanate 0.1-0.2 parts, pentaerythritol tetraacrylate 1.5-2.5 parts, N-phenyl maleimide 0.3-0.6 parts, each component is stirred and mixed at 25℃-30℃ for 8 min-15 min at a stirring rate of 300 r / min-400 r / min to obtain a uniform synergistic crosslinking agent; S4. The modified base resin particles obtained in step S2 and the synergistic crosslinking agent obtained in step S3 are added to a pressurized banbury mixer at a mass ratio of 100:6-100:9, and the mixture is mixed at a temperature of 115℃-130℃, a speed of 70 r / min-100 r / min, and a pressure of 0.4 MPa-0.8 MPa for 10 min-15 min, and nitrogen is purged every 3 min during the mixing process, with each purge lasting 30 s, to obtain a crosslinked premix; S5. The crosslinked premix obtained in step S4 is added to a single-screw extruder, the barrel temperature of the extruder is set to 125℃, 135℃, 145℃, 155℃ from the feeding end to the head direction, the screw speed is 180 r / min-280 r / min, the head temperature is 150℃-165℃, and the material is formed by an extrusion die with a die pressure of 18 MPa-28 MPa, and the extrusion speed is 12 m / min-25 m / min to obtain an insulating substrate; S6. The insulation substrate obtained in step S5 is subjected to segmented microwave pretreatment, the first segment has a microwave frequency of 2450 MHz, a power of 350 W~450 W, a treatment time of 2 min~4 min, and the substrate temperature is maintained at 65℃~70℃; the second segment has a microwave frequency of 915 MHz, a power of 400 W~550 W, a treatment time of 3 min~5 min, and the substrate temperature is maintained at 70℃~78℃; S7. The pretreated insulation substrate is placed in a sealed crosslinking reaction box, and pure nitrogen gas with a purity of 99.99% is introduced to replace the air in the box for 3 times, each time for 15 min. After the replacement is completed, saturated nitrogen gas with a humidity of 88%~96% is introduced into the reaction box, and the reaction temperature is controlled at 78℃~88℃, and the pressure in the box is controlled at 0.15 MPa~0.3 MPa. The crosslinking reaction is maintained for 5 h~9 h under the above conditions. S8. After the crosslinking reaction is completed, the nitrogen gas is kept flowing, the humidity in the reaction box is reduced to 45%~55% at a rate of 5% per hour, and the temperature is reduced to 30℃~35℃ at a rate of 3℃ / min~6℃ / min. The temperature is maintained for 40 min~70 min, then the nitrogen gas is stopped, and the temperature is naturally reduced to room temperature to obtain a crosslinked polyethylene insulation material.

2. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: The composite antioxidant system in step S1 is composed of a thio-hindered phenolic antioxidant, a phosphite antioxidant, and a hindered amine light stabilizer in a mass ratio of 3:2:

1.

3. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: The nano-silicon dioxide in step S1 is surface-grafted with methacryloxypropyltrimethoxysilane, the grafting rate is 8%~12%, and the particle size is 30 nm~60 nm.

4. A process for crosslinking of polyethylene insulation at low temperature according to claim 1, wherein: The ethylene-octene copolymer in step S1 is grafted with maleic anhydride, the grafting rate is 1.5%~2.5%, and the melt flow rate is 1.2 g / 10 min~2.0 g / 10 min.

5. A process for crosslinking of polyethylene insulation at low temperature according to claim 1, wherein: The length-diameter ratio of the twin-screw extruder in step S2 is 40:1, and the screw compression ratio is 3.5:

1.

6. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: The composite peroxide initiator in step S3 is composed of di-tert-butyl peroxide, 1,3-bis-tert-butyl peroxylisopropylbenzene, and 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane in a mass ratio of 2:1:

1.

7. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: The nitrogen gas purging pressure of the pressurized internal mixer in step S4 is 0.6 MPa~0.9 MPa.

8. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: The die orifice expansion ratio of the extrusion die in step S5 is 1.8:1~2.2:1, and the die temperature is maintained at 155℃~160℃.

9. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: The rate of the saturated nitrogen gas in the step S7 is 0.8 m 3 / h~1.8m 3 / h.

10. A process for crosslinking of crosslinked polyethylene insulation at low temperature as claimed in claim 1 wherein: In the crosslinking reaction process in step S7, the temperature and humidity are calibrated every 45 min by an online monitoring system, the temperature deviation is controlled within ±0.8℃, and the humidity deviation is controlled within ±2%.